2016
DOI: 10.3892/ol.2016.4596
|View full text |Cite
|
Sign up to set email alerts
|

Applications of nanoparticle drug delivery systems for the reversal of multidrug resistance in cancer

Abstract: Abstract. Multidrug resistance (MDR) to chemotherapy presents a major obstacle in the treatment of cancer patients, which directly affects the clinical success rate of cancer therapy. Current research aims to improve the efficiency of chemotherapy, whilst reducing toxicity to prolong the lives of cancer patients. As with good biocompatibility, high stability and drug release targeting properties, nanodrug delivery systems alter the mechanism by which drugs function to reverse MDR, via passive or active targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 60 publications
(63 reference statements)
1
27
0
1
Order By: Relevance
“…This distinct activity of drug‐loaded vesicles in DR‐HeLa cells was also evaluated 4 h post‐treatment and it was observed that CL1V–DOX or CL2V–DOX treatment led to clearly visible intracellular DOX fluorescence, whereas treatment with the free drug did not cause cells to fluoresce (Figure 6a1 and a) . This can be plausibly ascribed to the ability of nanocarriers to bypass the drug‐efflux pumps on the membrane of drug‐resistant cells, which results in an increased intracellular concentration of drug . The drug internalisation study also helped in understanding the observed cytotoxicity against both drug‐sensitive and drug‐resistant cancer cells, which apparently relied upon the intracellular accumulation of drug .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This distinct activity of drug‐loaded vesicles in DR‐HeLa cells was also evaluated 4 h post‐treatment and it was observed that CL1V–DOX or CL2V–DOX treatment led to clearly visible intracellular DOX fluorescence, whereas treatment with the free drug did not cause cells to fluoresce (Figure 6a1 and a) . This can be plausibly ascribed to the ability of nanocarriers to bypass the drug‐efflux pumps on the membrane of drug‐resistant cells, which results in an increased intracellular concentration of drug . The drug internalisation study also helped in understanding the observed cytotoxicity against both drug‐sensitive and drug‐resistant cancer cells, which apparently relied upon the intracellular accumulation of drug .…”
Section: Resultsmentioning
confidence: 91%
“…Towards achieving these therapeutic goals, the development of bioresponsive nanocarriers that respond to either exogenous (e.g., changes in temperature and magnetic field) or endogenous (e.g., changes in pH and redox potential) stimuli has been rigorously studied over the last ten years . Bio‐responsive systems have the potential to address key issues in anticancer therapy, such as inefficient drug delivery, tumour‐cell‐specific targeting and the development of resistance to chemotherapeutic drugs . The existing plethora of drug transport vehicles is composed of several types of nano‐ and micro‐structured self‐assemblies of amphiphiles .…”
Section: Introductionmentioning
confidence: 99%
“…In cancer Pgp is over expressed and contributes to multi drug resistance by pumping chemotherapeutic drugs out of the cells. Because the Pgp transmembrane domain (TMD) is capable to identify chemically unrelated molecules and translocate them, mainly which are hydrophobic because ABC transporters permeates hydrophilic substances to pass through (Chang, 2003;Huang et al, 2016). More than 50% of cancer patients arises multi drug resistance.…”
Section: Limitations Of Conventional Chemotherapymentioning
confidence: 99%
“…However, chemotherapy is associated with the unavoidable side effects, leading to toxicity to patients and development of drug resistance (14). The development of advanced drug delivery systems has shown great potential to yield enhanced therapeutic efficacy and comparatively higher accumulation of drug in tumor cells along with minimal exposure to normal tissues (1,5,6). However, the development of multidrug resistance (MDR) in cancer cells is of grave concern, limiting the efficacy of anticancer agents and, hence, the failure of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of multidrug resistance (MDR) in cancer cells is of grave concern, limiting the efficacy of anticancer agents and, hence, the failure of therapy. Several biochemical changes have been described to be involved for the development of MDR (57). Overexpression of ATP-binding cassette transporters causing efflux of drug, overexpression of P-glycoprotein (P-gp), multidrug resistance-associated proteins (MRP1, MRP2), and breast cancer resistance protein (BCRP) are some of the major mechanisms reported to be involved in the development of MDR (68).…”
Section: Introductionmentioning
confidence: 99%